Intent, implementation, impact. (2nd August 2021) - Caswell, Jo
Abstract : Settings are assessed on the quality of education they provide, which is their curriculum. This article explains what is meant by 'curriculum' and how leaders can be instrumental in designing a framework of learning tailored specifically for the children in their setting.